Sekularisme dan Identitas Muslim Eropa - Amin Mudzakkir (Jurnal Kajian Wilayah, 2013)
For most European countries, religious freedom is part of secularism principles to manage separation between public and private sphere. The right of citizens to believe and practice of religious faith, however, is not always synonymous with recognition from the state. In several countries, constitution guarantees religious freedom, but in some cases in European countries government has not yet been formally recognized the existence of Islam. In this context recognition is defined as recognition of organizations that represent religious community. The issue of representation is indeed very crucial, because this concerns distribution of public finances. Recognition of religious-based organizations means the states willingness to subsidize religious activities.The presence of migrants have made the issue of religious freedom is becoming more widespread in recent years. As the bulk of the migrants, Muslims are the most important subject in this issue. Prohibition of the use of religious symbols, including headscarves for Muslim women in public schools in France, has raised a number of questions about how far freedom of religion which based on secularism is practiced. Furthermore, questions about the meaning of secularism was critically raised back into the European public sphere. In fact, secularism is a political discourse that interpreted by various European countries. According to the observers, such diversity in the meaning of secularism is resulted come from the influence of dominant religious culture and political development of the nation-states project which is also different in each European country.On the other hand, different interpretation of secularism is also linked with political dynamics of migration of European countries. Muslims in Europe as immigrant become the targeted group of integration policy. The problem of integration is not just include politics in public life, but also in the cultural area of private life. In this context, debate on multiculturalism emerged as a reaction to the assimilationist view which want to merge cultural boundaries of migrants to European community. Questions about how far the state should interfere in the cultural life, including those of religious practices, migrants, in this case the Muslim immigrants, is an important issue as a focus in this paper.Keywords: secularism, Muslim, immigrants, Identity, Europe